2017
DOI: 10.1259/dmfr.20160452
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and contrast resolution of ultralow dose dentomaxillofacial CT imaging using iterative reconstruction technology

Abstract: Objectives: The objective of this study was to determine how iterative reconstruction technology (IRT) influences contrast and spatial resolution in ultralow-dose dentomaxillofacial CT imaging. Methods: A polymethyl methacrylate phantom with various inserts was scanned using a reference protocol (RP) at CT dose index volume 36.56 mGy, a sinus protocol at 18.28 mGy and ultralow-dose protocols (LD) at 4.17 mGy, 2.36 mGy, 0.99 mGy and 0.53 mGy. All data sets were reconstructed using filtered back projection (FBP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
0
20
0
8
Order By: Relevance
“…ASIR uses information obtained from the FBP algorithm as a scaffold for image reconstruction, while MBIR incorporates a number of key parameters . These iterative reconstruction (IR) algorithms are both reported as capable of reducing dose in facial bone imaging, while maintaining low noise and enhancing spatial and contrast resolution . Studies published by Widmann et al demonstrated that the implementation of adaptive statistical IR and model‐based IR in craniofacial bone imaging reduced dose by 76% and 91% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ASIR uses information obtained from the FBP algorithm as a scaffold for image reconstruction, while MBIR incorporates a number of key parameters . These iterative reconstruction (IR) algorithms are both reported as capable of reducing dose in facial bone imaging, while maintaining low noise and enhancing spatial and contrast resolution . Studies published by Widmann et al demonstrated that the implementation of adaptive statistical IR and model‐based IR in craniofacial bone imaging reduced dose by 76% and 91% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These iterative reconstruction (IR) algorithms are both reported as capable of reducing dose in facial bone imaging, while maintaining low noise and enhancing spatial and contrast resolution . Studies published by Widmann et al demonstrated that the implementation of adaptive statistical IR and model‐based IR in craniofacial bone imaging reduced dose by 76% and 91% respectively. The absorbed dose using adaptive statistical IR can be as low as 2.19 mGy, while for model‐based IR dose can be minimised to 0.22 mGy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 With MBIR, ultra-low-dose protocols at CTDI vol ϭ 4.14 and 2.63 mGy may show comparable scores for spatial resolution, which may allow a dose-reduction potential of up to 93%. 26 Compared with FBP, ASIR was not able to significantly improve spatial resolution. 26 In a more recent human cadaver study evaluating the influence of various low-dose protocols and IRTs on the detectability of midfacial fractures, ultra-low-dose protocols at CTDI vol ϭ 1.0 and 2.6 mGy were diagnostic for dislocated and nondislocated fractures, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…26 Compared with FBP, ASIR was not able to significantly improve spatial resolution. 26 In a more recent human cadaver study evaluating the influence of various low-dose protocols and IRTs on the detectability of midfacial fractures, ultra-low-dose protocols at CTDI vol ϭ 1.0 and 2.6 mGy were diagnostic for dislocated and nondislocated fractures, respectively. 14 However, due to smoothing effects, ASIR and MBIR could not improve fracture detection.…”
Section: Discussionmentioning
confidence: 96%